2021
DOI: 10.1016/j.ctro.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Abscopal effect in a patient with malignant pleural mesothelioma treated with palliative radiotherapy and pembrolizumab

Abstract: The abscopal effect describes the ability of locally administered radiotherapy to induce systemic antitumor effects. Although mentioned for the first time in the 1950s, records of abscopal effects, considered to be immune-mediated, are scarce with radiotherapy alone. However, with the continued development and use of immunotherapy, reports on the abscopal effect have become increasingly frequent during the last decade. Here, we report a patient with advanced malignant pleural mesothelioma who had progressive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…After 20 cycles he had progressive disease leading to administration of palliative RT (30 gray in 10 fractions) to the paramediastinal lesion. Imaging three months after RT demonstrated partial response to paramediastinal lesion as well as response to right pleura lesion, outside the RT field [7].…”
Section: Discussionmentioning
confidence: 97%
“…After 20 cycles he had progressive disease leading to administration of palliative RT (30 gray in 10 fractions) to the paramediastinal lesion. Imaging three months after RT demonstrated partial response to paramediastinal lesion as well as response to right pleura lesion, outside the RT field [7].…”
Section: Discussionmentioning
confidence: 97%
“…However, the number of reports of an abscopal effect in patients treated with a combination of radiotherapy and ICI has increased [7][8][9][10][11][12][13][14][15]. Only in one year of 2021, 21 case reports of abscopal effect promoted after radiotherapy were yielded [13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. This is thought to be due to T-cell activation by a damage signal from irradiated dying cells and upregulation of Programed death receptor-1 (PD-1) and programed cell death 1-Ligand 1 (PDL-1) [36,37], and an ICI disarms immune escape mechanisms, and this may increase the effects of the innate immune response activated by radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of a small series (17 cases) reported by Vicidomini et al suggested that two cycles of induction chemotherapy, followed by PD and postoperative RT 3–6 weeks seemed to be feasible with a median OS of about 32 months. 9 The role of RT is supposed to acquire greater relevance into the next future multimodal regimens due to both novel techniques and abscopal interaction with immunotherapy, 10 , 11 , 12 which is now going to play a significant role against MPM. 13 , 14 , 15 Although limited, our fundings highlight a rationale for local therapeutic delivery after a starting surgical approach with the aim, on one hand, of acting on the immunoinflammatory pathways which drive MPM progression 16 , 17 and, on the other hand, of limiting the systemic toxicities of chemo‐ and immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…• Mean (IQR) 11 (9-10) 14 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) Pleural thickness (mm) at surgical specimen have been obtained through MedCalc software for each cohort.…”
Section: Cigarette Smoking Habitmentioning
confidence: 99%